E Effectiveness of Consuming Boiled Eggs on Healing Time Perennial Wounds in Postpartum Mothers - Wulandari, Lusia Asih; Safitri, Eka Yuni; Yulianingsih, Wulan; Firawati, Nani; Farina, Farina; Sulinanda, Welia Rosa; Sulastri, Sulastri; Miswari, Miswari; indah, Sri (Fakultas Ilmu Kesehatan, 2024)
One of the causes of postpartum maternal deaths is infection in the perineal wound due to lack of adequate wound care, which causes secondary bleeding during the postpartum period, as well as triggering local and general infections. The impact of perienal suture wounds can cause infection and disruption of the mother's movements and activities. Accelerating wound healing during the postpartum period is highly expected, one of which is by consuming high levels of protein, namely eggs. This study aims to determine the effectiveness of giving boiled eggs on healing perineal wounds in postpartum mothers. The observation case study method using observation sheets and checklists with a continuity of care approach was given to postpartum mothers, Mrs. R at Adeyane Midwife Independent Practice, Tanggamus Regency from 30 December- 3 January 2024. Data analysis by comparing the data obtained with existing theory. Complementary midwifery care for postpartum mothers by consuming boiled eggs twice a day for a week or as long as the wound has not healed. As a result, giving postpartum mothers boiled egg whites will speed up the healing of perineal wounds. It is expected that providers of midwifery care services will always maintain existing midwifery services and continue to develop the latest knowledge.